Structure revision of trichotoxin, a chlorinated polyketide isolated from a Trichodesmium thiebautii bloom. Issue 52 (28th December 2016) - Bertin, Matthew J.; Zimba, Paul V.; He, Haiyin; Moeller, Peter D.R.
Graphical abstract: Highlights: We have re-isolated and revised the original structure of the trichotoxin. Comparison of spectroscopic data provides strong support for revision. We have isolated and characterized an analog, trichotoxin B. Abstract: NMR-guided fractionation of the lipophilic extract of Trichodesmium thiebautii filaments led to the isolation of a phenyl-containing chlorinated polyketide (1 ) and an alkyne-containing analog (2 ). Comparison of spectroscopic and spectrometric data of1 with the data of the previously reported trichotoxin, strongly suggested that these metabolites were identical and supports a structural revision of trichotoxin and its designation as trichotoxin A. In addition, we report the isolation and characterization of the alkyne-containing analog trichotoxin B (2 ). Absolute configuration of1 and2 is proposed based on spectroscopic comparison to a close structural analog.